2020
DOI: 10.1101/2020.12.17.20248234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Airflow and air velocity measurements while playing wind instruments, with respect to risk assessment of a SARS-CoV-2 infection

Abstract: Due to airborne transmission of infection with the coronavirus, the question arose as to how high the risk of spreading infectious particles can be while playing a wind instrument.To contribute to this question and to help clarify the possible risks, we analyzed 14 wind instruments, first qualitative by making airflows visible while playing and second quantitative by measuring air velocities at three distances (1m, 1.5m and 2m) in direction of the instrument’s bell.Measurements took place with wind instrumenta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…An online preprint suggests mitigation strategies to reduce exposure to aerosols produced by playing musical instruments (Stockman et al 2021). Several preprints of manuscripts under review have explored air flows emanating from musical instruments to suggest appropriate distancing guidelines (Kähler and Hain 2021;Becher et al 2020;Spahn et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An online preprint suggests mitigation strategies to reduce exposure to aerosols produced by playing musical instruments (Stockman et al 2021). Several preprints of manuscripts under review have explored air flows emanating from musical instruments to suggest appropriate distancing guidelines (Kähler and Hain 2021;Becher et al 2020;Spahn et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By placing a burning candle at 0.5 m in front of the singer's mouth, it was observed that the flame hardly moved due to only small disturbances of the exhaled air 11,12 . For playing wind instruments, Spahn et al 13 concluded that the air escaping from either the bell, the tone holes, or the mouthpiece of the instruments does not move farther than 1.5 m. For wind instruments, the exhalation of air is similar to singing: the aim is to use as little as possible breathing air to allow the vocal cords (singing), reeds (woodwind), or the lips (brass) to vibrate and stimulate the air column inside the instrument 11…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies measured air velocity and movement emerging from wind instruments using photography, Schlieren optics, sensors in the vicinity of the musician and Particle Image Velocimetry [10,11,12,13,14]. The latter observed airflow up to .5 m from the bell of brass instruments like trumpet, trombone and euphonium.…”
Section: Introductionmentioning
confidence: 99%